Flammability and physical stability of sugar palm crystalline nanocellulose reinforced thermoplastic sugar palm starch/poly(lactic acid) blend bionanocomposites - Asmawi, Nazrin; Salit, Mohd Sapuan; Mohamed Yusoff, Mohd Zuhri; Mohamed Amin Tawakkal, Intan Syafinaz; Rushdan, Ahmad Ilyas (Walter de Gruyter GmbH, 2022)
In this study, sugar palm crystalline nanocellulose (SPCNC)-reinforced thermoplastic sugar palm starch (TPS) was blended with poly(lactic acid) (PLA) in order to prioritize the biodegradation feature while offsetting individual polymer limitation. Prior to melt blending process, SPCNC was dispersed through sonication in advance of starch gelatinization which was later casted into petri dishes. PLA and TPS were melt blended into five different ratios using Brabender mixer followed by compression molding. Soil degradation (4 months) and water uptake (4 weeks) tests were conducted to evaluate the physical stability of PLA/TPS blend bionanocomposites. Based on Fickian law, the diffusion curve and coefficient of diffusion for seawater, river water, and sewer water were calculated. The flammability and limiting oxygen index (LOI) tests were conducted in accordance with ASTM D635 and ASTM D2863, respectively. For PLA60TPS40 (40% TPS), significant reduction (46–69%) was recorded in maximum water uptake in all mediums, while soil degradation rate experienced insignificant increment (7.92%) for PLA70TPS30 (30% TPS) owing to the reinforcement of SPCNC through the well-dispersed TPS within PLA. Meanwhile, the flammability rates and LOI values for PLA40TPS60 and PLA60TPS40 indicated flammable material properties.